FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI SUSU SAPI PERAH DI KECAMATAN MEGAMENDUNG KABUPATEN BOGOR PROVINSI JAWA BARAT - Rina Karuniawati; Anna Fariyanti (Forum Agribisnis, 2013)
The dairy cow is one of the lifestock commodity still have potential to develop in Indonesia. The domestic milk production only cover 1/3 of domestic demand so the  most of  milk remains were still imported. Cipayung village, District Megamendung, Bogor regency is one of the central production for fresh milk. The problems that faced by the most of farmers in this region are the low productivity of milk, it’s about 8-10 litre/day so it’s can influence to the income level of farmers too. The purpose of this research are  to analyze about factors that have affected to the production of milk and to analyze income of dairy cow farm. This research used Cobb Douglas production function with the respondents were 35 dairy farmers members of Mekar Jaya Farmer Group. The respondents in this research were chosen by purposive sampling method where  leader of the farmer group has an estimation to choose the farmers that have qualification become a respondent. Based on the results of analyzed research showed that period of lactation, forages, water and labors were factors that have significantly affected to the production of dairy cows. This analyze also showed that the value of farm R/C ratio of the cash cost was1,64 and R/C ratio of the total cost was 1,25.